Water entry of spheres into a rotating liquid. (4th February 2021) - Yi, Lei; Li, Shuai; Jiang, Hechuan; Lohse, Detlef; Sun, Chao; Mathai, Varghese
Abstract: Abstract : The transient cavity dynamics during water entry of a heavy, non-rotating sphere impacting a rotating pool of liquid is studied experimentally, numerically and theoretically. We show that the pool rotation advances the transition of the cavity type – from deep seal to surface seal – marked by a reduction in the transitional Froude number. The role of the dimensionless rotational number $\mathcal {S} \equiv ω R_0/U_0$ on the transient cavity dynamics is unveiled, where $R_0$ is the sphere radius, $ω$ the angular speed of the liquid and $U_0$ the impact velocity. The rotating background liquid has two discernible effects on the cavity evolution. Firstly, an increase in the underwater pressure field due to centripetal effects; and secondly, a reduction in the pressure of airflow in the cavity neck near the water surface. The non-dimensional pinch-off time of the deep seal shows a robust $1/2$ power-law dependence on the Froude number, but with a reducing prefactor for increasing $ω$ . Our findings reveal that the effects of a rotating background liquid on the water entry can be traced back to the subtle differences in the initial stage splash and the near-surface cavity dynamics.